Healthy food discourse in language learning: Analysing nutritional content in ELT materials - Widi Pratolo Bambang; Purwanti Eko; Bao Dat; Daifullah Alsulami Naif; Dwi Hatmanto Endro; Wulandari Yosi; Setyo Humanika Eko (BIO Web of Conferences)
This study examines the representation of healthy food discourse in English Language Teaching (ELT) textbooks, addressing the intersection of language education and nutritional awareness. As ELT materials play a crucial role in shaping learners’ linguistic and cultural knowledge, understanding how they present health-related content is vital. The research aims to analyze the explicit and implicit messages about healthy eating in ELT textbooks, evaluate the integration of nutritional information with language learning objectives, and explore potential cultural biases in food representation. Employing a qualitative approach, this study utilizes critical discourse analysis to examine ELT textbooks Bahasa Inggris: Work in Progress untuk SMA/SMK/MA Kelas X published in 2022 by Indonesian ministry of education. The methodology involves systematic content identification and multi-layered discourse analysis. The findings reveal varied approaches to healthy food representation, cultural disparities in nutritional content, and the extent of alignment between food-related discourse and current health guidelines. The implications of this research could inform future ELT material development, enhancing the integration of health literacy within language education. This study contributes to the growing field of content-based language instruction and provides insights into the broader sociocultural impacts of ELT materials on learners’ health awareness. In the end, an activity is proposed for students to experience a vibrant sample of ELT materials on food and health that are discussed throughout the article.